1997
DOI: 10.1097/00006534-199703000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Maxillofacial Treatment of Obstructive Sleep Apnea

Abstract: Obstructive sleep apnea is the most common sleep-related breathing disorder, with a surprisingly high prevalence. The treatment of choice is nasal continuous positive airway pressure (CPAP) ventilation during sleep, which has to be applied throughout the patient's whole life. Because of various underlying pathomechanisms in patients with certain craniofacial disorders--narrow posterior airway space and maxillary-mandibular deficiency--surgical therapy by craniofacial osteotomies seems possible. A series of 38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0
13

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(84 citation statements)
references
References 4 publications
2
69
0
13
Order By: Relevance
“…The indications for this procedure are determined by cephalometric and polysomnographic studies. [26][27][28] Ö zbek et al 19 studied the effects of functional-orthopedic treatment on oropharyngeal dimensions of growing patients with Class II malocclusion, and concluded that sagittal dimensions of the upper airway could be increased by functional treatment. Considering that mandibular growth has a definite influence on upper airway dimensions, one may speculate that stimulation of maxillary growth in growing subjects with a retrusive maxilla could also have beneficial effects on the upper airway dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…The indications for this procedure are determined by cephalometric and polysomnographic studies. [26][27][28] Ö zbek et al 19 studied the effects of functional-orthopedic treatment on oropharyngeal dimensions of growing patients with Class II malocclusion, and concluded that sagittal dimensions of the upper airway could be increased by functional treatment. Considering that mandibular growth has a definite influence on upper airway dimensions, one may speculate that stimulation of maxillary growth in growing subjects with a retrusive maxilla could also have beneficial effects on the upper airway dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…When CPAP adherence is defi ned as > 4 hours of nightly use, 46% to 83% of OSA Several short term observational studies show that maxillomandibular advancement surgery (MMA) may be a clinically effective alternative therapy for patients with moderate-to-severe OSA who are not effectively treated with CPAP. [19][20][21][22][23][24][25][26] MMA involves surgical facial advancement by concomitant maxillary and mandibular osteotomies, thus enlarging the caliber of the posterior upper airway space. Although the level of evidence is low, substantial and consistent short-term reductions in the apnea-hypopnea index (AHI) are observed following MMA.…”
mentioning
confidence: 99%
“…Riley et al [65] reported the largest MMA series with success rate of 98%. In 2004 Dattilo and Drooger [66] reported 93% success rate in 14 of 15 cases, whereas Hochban et al in 1997 reported 97% success rate in 37 of 38 cases [67].…”
Section: Maxillomandibular Advancementmentioning
confidence: 98%